On a doped transition layer in the space charge region of Schottky contact - Shekhovtsov, L.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
A technique is proposed for estimation of maximal thickness of a doped semiconductor transition layer in a Schottky contact. It is based on taking spectral curves of transverse photovoltage. It is shown that in gallium arsenide crystal with starting impurity concentration of 10¹⁶ cm-³, a layer with doping level of 10¹⁷ cm-³ and maximal thickness of 4 nm may exist in the space-charge region near the interface of the TiB₂-GaAs structure. At impurity concentration in the transition layer about and over 101¹⁸ cm-³, its thickness goes down, and it shows up as individual inclusions in the GaAs lattice. The total area of such inclusions at the metal-semiconductor interface does not exceed 1 % that of contact. In actual structures the transition layer is a superposition of layers and inclusions, with impurity concentration of 10¹⁷ cm-³ or more and thickness below 4 nm.